2019
DOI: 10.3126/ajms.v10i2.22762
|View full text |Cite
|
Sign up to set email alerts
|

Ear Findings and Hearing analysis in cleft palate patients in Nepal

Abstract: Background: The orofacial cleft is the most common birth anomaly with a prevalence rate ranging from 1/1000 to 2.69/ 1000. The middle ear diseases are known to be associated with cleft palate, however, the prevalence and the magnitude of the condition is usually underestimated. Aims and Objectives: The purpose of this study was to find out the various exisiting ear abnormalities, to assess the middle ear function and hearing status  in patients with cleft palate and confirm the existence of these manifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Male to female ratio in this work is 1:1. This finding of improvement of hearing with increasing age is similar to other studies done [14][15][16][17][18][19][20] . A similar prospective study used pure tone audiometry alone as a tool for hearing assessment 11 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Male to female ratio in this work is 1:1. This finding of improvement of hearing with increasing age is similar to other studies done [14][15][16][17][18][19][20] . A similar prospective study used pure tone audiometry alone as a tool for hearing assessment 11 .…”
Section: Discussionsupporting
confidence: 91%
“…This means that, Eustachian tube (ET) dysfunction, palatine muscle abnormalities, and middle ear problems may still occur irrespective of the type of cleft palate. Thakur and co-workers found that, majority 72 (68.6%) of abnormal Pure Tone Audiometry was mild conductive hearing loss 17 which also revealed that 10 (9.5%) ears had moderate conductive hearing loss, 1 (1%) had mixed hearing loss and 22 (20.9%) had normal hearing which contradicts the findings of this research.…”
Section: Discussioncontrasting
confidence: 86%
“…59 However, there seems to be a variability in available reports which may be due to factors such as the mode of screening for hearing loss, race, presence of other congenital abnormalities, and patients age at time of treatment. [60][61][62] Lithovius et al reported prevalence as low as 3.3% using pure tone audiometry, Viswanathan et al reported prevalence as high as 82% using Auditory Brainstem Audiometry. 35,37 Giordano et al 63 found a prevalence of 17% among children with non syndromic cleft among Chinese children.…”
Section: Discussionmentioning
confidence: 99%